Melioidosis of the central nervous system; A potentially lethal impersonator. (2021) - Owen, William; Smith, Simon; Kuruvath, Sarin; Anderson, David; Hanson, Josh
Abstract: A 57-year-old Australian woman, with a history of hazardous alcohol consumption, presented with a seizure following 2 days of fever and headache. Initial imaging suggested the presence of an isolated brain abscess, however, a thorough physical examination, identified no additional septic focus. Five sets of blood cultures were sterile and serology for Burkholderia pseudomallei was negative. Other investigations including computed tomography of her chest, abdomen and pelvis and a trans-esophageal echocardiogram were normal. Despite the administration of intravenous vancomycin, ceftriaxone, and metronidazole, her condition deteriorated. At emergency craniotomy, the abscess was drained and B. pseudomallei was cultured, confirming a diagnosis of melioidosis. She received 8 weeks of intravenous meropenem, combined with oral trimethoprim/sulfamethoxazole; the trimethoprim/sulfamethoxazole was continued for a total of 12 months. She recovered completely and was able to return to full-time work. Melioidosis, is endemic to Australia and South East Asia and, globally, is estimated to kill 89, 000 every year. It can affect almost any organ, but up to 5% have central nervous system (CNS) involvement, where it may present as an encephalomyelitis, brain abscess or meningitis. B. pseudomallei is resistant to many commonly used antibiotics and even in well-resourced settings the case-fatality rate of CNS infection may rise to 50 %. This patient lived in a melioid-endemic region, and, with hazardous alcohol consumption, had a classical risk factor for the disease, but the sterile blood cultures and negative B. pseudomallei serology delayed definitive therapy. Despite the delayed diagnosis, definitive drainage and prolonged anti-bacterial therapy ensured a complete recovery.